1966
DOI: 10.1111/j.1348-0421.1966.tb00304.x
|View full text |Cite
|
Sign up to set email alerts
|

Infection of Cattle with Parainfluenza 3 Virus with Special Reference to Udder Infection

Abstract: Thirty-seven strains of parainfluenza 3 virus were isolated on bovine kidney cell cultures from Japanese cattle in herds suffering from acute respiratory illness. This finding, together with the clinical and epidemiologic observations and the results of a serologic survey, indicates that in Japan, as in the United States and other countries, this virus is one of the important causes of acute respiratory disease in cattle. A significant finding in the present study is that virus was recovered from milk as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
15
0

Year Published

1966
1966
2002
2002

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 5 publications
1
15
0
Order By: Relevance
“…An occurrence of EHV-1 abortion among imported mares in 1967 caused the first outbreak of EHV-1 abortion among pregnant mares raised in Japan [5]. Thereafter both EHV-1 and -4 spread among various horse populations in Japan.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…An occurrence of EHV-1 abortion among imported mares in 1967 caused the first outbreak of EHV-1 abortion among pregnant mares raised in Japan [5]. Thereafter both EHV-1 and -4 spread among various horse populations in Japan.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] in which a tentative serological diagnosis of EHV-1 or -4 infection was made by complement fixation (CF) test. The result showed that a final diagnosis of EHV-1 infection was made in 8 horses and that diagnosis of EHV-1 infection might be made in another 3 horses (Table 1).…”
mentioning
confidence: 99%
“…Strain BNM-7 of parainfluenza type 3, one of the isolates from milk reported in our previous paper [6], was employed. Fluids from infected bovine kidney cell cultures at the 7th to 10th passages were used as the inoculum.…”
Section: Methodsmentioning
confidence: 99%
“…Fluids from infected bovine kidney cell cultures at the 7th to 10th passages were used as the inoculum. Assays of virus and of neutralizing and hemagglutination-inhibiting (HI) antibodies were carried out by the methods described in the previous report [6].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation